PO019 Contractures and glycine receptor antibody encephalitis. (1st December 2017) - Salim, Omar; McDonald, Menai; MacDougll, Niall; Davidson, Amy
Abstract : 68 year lady with 3 weeks of dysphagia, intermittent diplopia and bilateral ptosis. MRI brain and AChR antibody were normal. This progressed into multiple cranial nerve and cerebellar signs with symmetrical pyramidal weakness. Reflexes were globally brisk with increased tone. Autonomic dysfunction was noted, but no abnormal movements. She aspirated and had a prolonged cardiac arrest. This complicated her neurology causing a mild left hemiparesis from watershed infarct. Lyme, blood-borne viruses and syphilis testing, alongside a wide panel of auto-antibodies were negative. CSF protein was mildly raised (0.55 g/L) and WCC of 11 with negative viral PCR. Nerve conduction studies showed no evidence of peripheral neuropathy or neuromuscular junction dysfunction. Repeat Brain MRI was normal. 4 months after spontaneous improvement, she relapsed with complex ophthalmoplegia, severe bulbar weakness, fluctuating conscious level, and marked spasticity that rapidly evolved into severe ankle contractures requiring multiple Botox injections. Further investigations revealed Glycine receptor antibody was strongly positive in serum and CSF. She recovered well on steroids, plasmapheresis and Rituximab. Light has recently been shed onto the link between Glycine receptor antibody and brainstem and spinal cord disorders. The clinical presentation can vary from Stiff Person Disorder to Progressive Encephalomyelitis with Rigidity and Myoclonus (PERM).